Caffeine and exercise performace - Graham, T. E.; Spriet, L. L. (1996)
1. Recent, well-controlled studies have established that moderate doses of caffeine ingested 1 h prior to exercise enhance the performance of certain types of endurance exercise in the laboratory. Moderate caffeine doses produce urinary caffeine levels well below the allowable limit, as determined by the International Olympic Committee. The results are specific to well-trained elite or recreational athletes. It is not known if these findings will improve performance in competitions because controlled field studies of the effects of caffeine are lacking.